Commander Toad and the space pirates - Yolen, Jane frey50; Degen, Bruce (New York : Coward-McCann, 1987)
When Commander Salamander and his band of pirates capture the "Star Warts" spaceship, Commander Toad is forced to hop the plank.
77078
Keywords: Toads -- Fiction; Pirates -- Fiction; Science fiction